Rate Dependent Multicontinuum Progressive Failure Analysis of Woven Fabric Composite Structures under Dynamic Impact - James Lua; Christopher T. Key; Shane C. Schumacher; Andrew C. Hansen (Shock and Vibration)
Marine composite materials typically exhibit significant rate dependent response characteristics when subjected to extreme dynamic loading conditions. In this work, a strain-rate dependent continuum damage model is incorporated with multicontinuum technology (MCT) to predict damage and failure progression for composite material structures. MCT treats the constituents of a woven fabric composite as separate but linked continua, thereby allowing a designer to extract constituent stress/strain information in a structural analysis. The MCT algorithm and material damage model are numerically implemented with the explicit finite element code LS-DYNA3D via a user-defined material model (umat). The effects of the strain-rate hardening model are demonstrated through both simple single element analyses for woven fabric composites and also structural level impact simulations of a composite panel subjected to various impact conditions. Progressive damage at the constituent level is monitored throughout the loading. The results qualitatively illustrate the value of rate dependent material models for marine composite materials under extreme dynamic loading conditions.